Anti-tumor role and molecular mechanism of vanillic acid - Xunxing Hao; Zhixiao Gao; Mingzhe Hu (Discover Oncology)
Abstract Vanillic Acid (VA) is an aromatic acid extracted from traditional Chinese medicine such as Angelica sinensis and Panax ginseng, which has demonstrated potent anti-cancer activity, inhibiting the onset and progression of various malignant tumors. This review highlights the principal mechanism by which VA exerts its anticancer activity, including apoptosis induction, specifically promoting the generation of intracellular reactive oxygen species (ROS), which in turn triggers mitochondrial apoptosis. Furthermore, VA disrupts the cancer cell cycle, arresting most cancer cells at the G1 phase, curtails cell migration, invasion, angiogenesis, and potentiates the therapeutic efficacy of chemotherapeutic drugs, all while minimizing adverse reactions. This paper offers a comprehensive review of VA's anti-tumor effects and underlying mechanisms, aiming to provide some references for scientists and clinical physicians in the research of anti-tumor therapeutic strategies.